Effects of Online Learning on Student Moral Development: A Meta-analysis Based on 42 Experimental and Quasi-experimental Studies - Wang, Hao; Tang, Aimin (Best Evidence in Chinese Education, 2023)
The widespread practices of online learning have sparked increasing interest in its educational efficacy. The effects of online learning on learners’ moral development remain contentious in existing research. The purpose of this meta-analysis was to ascertain how online leaning impact students’ moral development. It included 42 experimental and quasi-experimental studies with an aggregate sample of 5303 learners after the processes of literature screening, data extraction, and risk of bias assessment. Analytical results revealed that online learning had positive effects on student moral understanding and reasoning, but no significant impact on student moral emotions and behavior. Subgroup analyses by student type, course type, online learning pattern, and involvement of interactive activity showed that there were disparities in the effect size between all subgroups and that only the moderating effect of student type on student moral reasoning was statistically significant.